A zero-risk weight channel of sovereign risk spillovers - Kirschenmann, Karolin; Korte, Josef; Steffen, Sascha (Journal of Financial Stability, 2020)
European banks are exposed to a substantial amount of risky sovereign debt. “Missing capital” in the banking system resulting from the zero-risk weight exemption for European sovereign debt amplifies the co-movement between sovereign CDS spreads and facilitates cross-border crisis spillovers. Risks spill over from risky peripheral sovereigns to safer core countries, but not in the opposite direction nor for exposures to countries not exempted from risk-weighting. Unfunded non-domestic sovereign bond exposures primarily affect CDS spreads of non-GIIPS banks, while domestic sovereign-to-bank linkages are particularly important for GIIPS banks. Spillovers are attenuated when banks fund their sovereign bond exposures with capital.